Functional evaluation of lung by Xe-133 lung ventilation scintigraphy before and after lung volume reduction surgery (LVRS) in patients with pulmonary emphysema - Kurose, Taichi; Okumura, Yoshihiro; Sato, Shuhei; Yamamoto, Yasuhiro; Akaki, Shiro; Takeda, Yoshihiro; Kanazawa, Susumu; Ando, Akio; Date, Hiroshi; Shimizu, Nobuyoshi; Hiraki, Yoshio (Acta medica Okayama, 2004)
We evaluated the respiratory functions of patients with pulmonary emphysema who underwent lung volume reduction surgery (LVRS) by the mean transit time (MTT) with Xe-133 lung ventilation scintigraphy, forced expiration volume in 1 sec (FEV1.0), residual volume (RV), distance walked in 6 min (6-min walk), and the Hugh-Jones classification (H-J classification) before and after LVRS. In 69 patients with pulmonary emphysema (62 men, 7 women; age range, 47-75 years; mean age, 65.4 years +/- 6.1, preoperative H-J classification, III (two were II)-V) who underwent LVRS, all preoperative and postoperative parameters (MTT 3 weeks after LVRS and the others 3 months after LVRS) were judged statistically by the Wilcoxon signed-ranks test and Odds ratio. Every postoperative parameter was improved with a significant difference (P < 0.05) compared to preoperative parameters. MTT at 3 weeks after LVRS was not associated with %FEV1.0 and the H-J classification at 3 months after LVRS, but was associated with RV and a 6-min walk at 3 months after LVRS. MTT was useful for the clinical evalution of aerobic capability after LVRS.